KARAKTER AGRONOMI GENOTIPE GANDUM (Triticum Aestivum L.) PADA LAHAN TROPIS DATARAN RENDAH DI INDONESIA - Theresa Dwi Kurnia; Nugraheni Widyawati; Djoko Murdono; Endang Pudjihartati (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2016)
ABSTRACTDevelopment of tropical wheat that suitable to low altitude is important in Indonesia. Aims of the research was to determine agronomic traits and select of wheat genotypes adaptive to tropical lowland. Three years study was conducted by planting ten wheat genotypes in Tlogoweru village, Guntur Subdistrict, Demak, Central Java at the altitude + 20 meters above sea level, from 2013 to 2015. From ten wheat genotypes planted in 2013, five wheat genotypes were considered adaptive, i.e., ALTAR, BASRIBEY, LAJ3302, OASIS and SELAYAR. In 2014 four genotypes were selected, they are ALTAR, BASRIBEY, LAJ3302 and OASIS. Finnaly, in 2015 genotype ALTAR was prominent candidate for the lowland tropical wheat varieties in study site. Among genotypes ALTAR had highest plant height, seed weight per panicle, number of seeds per panicle, number of productive tillers and yield estimates.